Mengintegrasikan Teknologi Informasi dan Komunikasi dalam Pengajaran Bahasa Inggris di Pendidikan Tinggi - Gloria Gloria; Barli Bram (Journal of Education and Teaching (JET), 2025)
In English Language Teaching, the differences in technology integration between novice and experienced teachers may affect the effectiveness of English teaching methods, students’ engagement in the class, and overall students’ learning outcomes. This study investigated the differences between English novice and experienced teachers’ ICT knowledge and use level and challenges. Four novice and seven experienced English teachers working in different high schools volunteered in this study. The researchers employed a qualitative design using a questionnaire and an in-depth interview as research instruments The findings showed that novice and experienced English teachers were confident in accessing the Internet and using ICT tools. They were well-informed about various ICT tools and techniques for English teaching. The difference was that novice English teachers showed high confidence and innovatively used ICT, whereas experienced English teachers were uncertain and cautious, sometimes relying on students’ assistance and considering some aspects such as students’ backgrounds and familiarity with ICT. Both English novice and experienced teachers used ICT, including learning websites, search engines, educational games, and multimedia presentations for class discussions, student assessments, brainstorming, and group projects to make the class interactive. This study has implications for English teachers, educators, and future researchers.